KAJIAN INTERTEKSTUALITAS NOVEL LINGKAR TANAH LINGKAR AIR KARYA AHMAD TOHARI DENGAN SENAPAN TAK BERPELURU KARYA JOKO GESANG SANTOSO - Luluk Nur Indah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
The research entitled "Intertextuality Study of Novel of Circumference of Land of Water Circle of Work of Ahmad Tohari with Unscrewed Rifle by Joko Gesang Santoso." The discussion raised by the researcher is about studying intertextuality that is the relation between the old literary works which become the foundation of the next literary work. This research focuses on the values ??of literary works including social values, nationalism value, religious values, and cultural values ??contained in Ahmad Tohari's Circle of Land Circle of Water with the Unscrewed Rifle by Joko Gesang Santoso. The novel relationship of Lingkar Tanah Air Circle of Work by Ahmad Tohari with the Unskilled Rifle by Joko Gesang Santoso, and the relevance of literature with literary learning.The method used in this study is descriptive qualitative which is telling, explaining or giving, analyzing, and classifying about the symptoms that are in question.The story of the character on Ahmad Tohari's Lingkar Tanah Lingkar Air novel and the novel Tak Berpeluru Gunman by Joko Gesang Santoso are examples of literary works that have a relationship with each other. Both of these novels are drawn from more or less the same source, the life of a state defender. Story in the novel background of the period of struggle by the character to be given to his country. The depiction of the stories in the two novels is so alive, according to what ever happened in that country. Keywords: Intertextuality, literary value.